Corrosion Inhibition Of Mild Steel In 1m HCL By Catechin Monomers From Commercial Green Tea Extracts - Nofrizal Nofrizal (Testing Center for Oil and Gas LEMIGAS, 2012)
The inhibitory effect of two Indonesian green tea extracts (containing various catechins) were investigated on the corrosion of mild steel (MS) in 1M HCl medium. The anticorrosion effect was evaluated by conventional weight loss method, potentiodynamic polarisation, electrochemical impedance spectroscopy (EIS) studies and scanning electron microscopy (SEM) technique. The results evidenced that both the tea extracts act as a good corrosion inhibitor and the inhibition effi ciencies (% IE) were in good agreement for all the studies. Adsorption of green tea extract constituent was found to follow Langmuir adsorption isotherm and the calculated Gibb’s free energy values indicated the physisorption of inhibitor over the mild steel surface. SEM – EDX studies show the adsorption of catechin monomers which forms a protective layer over the mils steel surface. High performance liquid chromatography (HPLC) analysis was carried out to quantify the catechin fractions in the tea extract and it was found that eight catechin monomers were present in both tea extracts. From all of monomers, it was found that four monomers were identifi ed as components responsible for controlling the dissolution of mild steel in 1 M HCl medium.